ASSESSMENT OF SOIL LOSS POTENTIAL THROUGH THE GEOGRAPHICAL INFORMATION SYSTEM (GIS) FOR THE PRIORIZATION OF RURAL ROADS IN THE MUNICIPALITY OF OURO VERDE / SP - Martin, Paulo Sergio [UNESP]; Tommaselli, Jose Tadeu Garcia [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
This work aimed to identify all the variables of soil loss potential risk condition in the municipality of Ouro Verde / SP. Therefore, along with identifying unsafe road sections to make the necessary adjustments, taking into account the nature of soil classification, geology, relief rainfall, land use and occupation, conservationists influence and cross-referencing to different information about current approach for unpaved road condition. The visual interpretation of the study area was performed on the basis of an assessment of Sentinel-2 satellite imagery. Municipal areas mappings has been carried out with cross-checks of information through application of the Universal Soil Loss Equation (USLE) and the InVEST (R) program which has estimated the losses from soil erosion. In order to recognize and prioritize high-risk road stretches, it was inferred parameters of structures and situations, adapted from the Sustainable Rural Development Project - Hydrographic Microbasins II, obtaining full framework of Classes prioritization criteria. The result of prioritizing unpaved roads identified those that, in their total extent or stretches, which need immediate, medium-term and long-term action, enabling public administrators in the City Hall and FEHIDRO to use this guide as source of analysis and decision-making The InVEST (R) program made possible to explore scenarios with probable future results, and thus various erosion potentiality maps were generated.
Keywords: Geographic Information System (GIS); Universal Soil Loss Equation (USLE); Rural Roads; InVEST; Soil Loss potential